The Effect of Soft Core Fruit Tree Leaves on Some Soil Properties - AYDEMİR, Murat and KARA, Zekeriya (ISPEC Journal of Agricultural Sciences, 2023)
The main purpose of this study is to investigate the effects on soil moisture constants (TK, YS), soil porosity (f) and penetration resistance (PNTR) as a result of recycling leaves of pome fruit trees to soil. For this, relevant measurements and samples were taken from the orchards where apple, pear, quince and date palm trees were grown and at the control point and necessary analyzes were made. According to the results obtained from the study, the soil variables OM, TK, f, YS increased, while HA, pH and PNTR decreased compared to the control point. These increases and decreases in the soils of pome fruit tree orchards were statistically significant compared to the control (p<0.05). On the other hand, apple and quince tree leaves showed the most effect on soil properties, and pear tree leaves showed the least effect. This was associated with the organic matter content of pome fruit tree leaves. As a result, the return of plant wastes to the soil improved the physical properties of the soils. Considering the most physical improvement in the soil, we can recommend other pome fruit (apple, quince, date) trees other than pear trees to those who want to grow garden plants.